Impact of Coal Sales on Revenue Sharing Fund And Environment in The South Sumatra Province - Fettymia Fettymia; Eddy Ibrahim; Didik Susetyo (Sriwijaya Journal of Environment, 2018)
Abstract. Coal prices between 2006-2015 trend was fluctuate but tend to decrease every year and affect regional income, especially South Sumatra Province. Coal prices fluctuation are influenced by several factors, the decline of world oil prices, coal production surplus, and China imports restriction. Coal mining industry also give a direct impact to the environment especially effect to work environment for the company workers and the people environment around mining. The coal mining company absorbs local labor so as to increase local revenues from individual income taxes. This research use quantitative approach using Ordinary Least Square (OLS) analytical method with E-views 7 software.  Multiple linier regression technique also applied.  The Secondary data is time series of 2006 - 2015. The results presented in form of tables, images and narration. From this research can be drawn conclusion that price fluctuations have no effect on regional income, but production sold has an effect on regional income. Keywords: Sale, price, royalty, Personal Income Tax Article 21, and Personal Income Tax Article 25/29 Abstrak (Indonesian)Harga batubara kurun 2006-2015 mengalami fluktuasi sehingga berpengaruh terhadap pendapatan Provinsi Sumatera Selatan. Fluktuasi harga batubara dipengaruhi oleh beberapa hal yaitu menurunnya harga minyak dunia, adanya kelebihan produksi batubara, dan pembatasan impor batubara oleh Cina. Industri pertambangan batubara memberikan dampak terhadap lingkungan salah satunya tenaga kerja. Perusahaan pertambangan batubara menyerap tenaga kerja lokal sehingga meningkatkan pendapatan daerah dari pajak penghasilan perorangan. Penelitian ini merupakan penelitian kuantitatif dengan metode analisis yang digunakan Ordinary Least Square (OLS) dengan software E-views 7.0. Teknik analisa data secara regresi linier berganda. Data sekunder merupakan time series periode tahun 2006 – 2015. Data dan hasil penelitian disajikan dalam bentuk tabel dan gambar serta narasi untuk menginterpretasikan data tersebut. Dapat disimpulkan fluktuasi harga tidak berpengaruh terhadap pendapatan daerah, tapi produksi terjual berpengaruh terhadap pendapatan daerah. Kata Kunci : Penjualan, harga, royalti, PPh pasal 21, dan PPh Pasal 25/29.